Toxic humans : Combatting poisonous leadership in boards and organisations - Jenkins, Michael (Emerald Publishing Limited, 2024)
International leadership expert Michael Jenkins shines a light on the adverse effects of dysfunctional and toxic boards and how they have the potential to destroy an organisation's culture. This can happen through erosion of brand value leading to talent attrition and increased mental health issues in employees due to a deterioration in trust and psychological safety. Combined with recent fundamental changes in the labour market and demographic changes in the workforce, there is a potent cocktail of Future of Work issues that will not go away. Enlightened leaders must tackle such issues head-on if they are to steward sustainable and responsible organisations and businesses. Based on extensive research, including interviews with board members from around the world, together with one-to-one interviews with leaders from the VAB (Virtual Advisory Board) network, Toxic Humans: Combatting Poisonous Leadership in Boards and Organisations outlines various experiences of toxic leadership and how successful directors managed to work with and through it. These interviews shape the final sections of the book where the reader is given a set of recommendations for action to help mitigate and manage the effect of toxic leadership - at the Board, senior leader and team levels - and to build a positive and productive workplace where all can flourish.
Includes index.
Keywords: Leadership.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books